Inhibition of spoilage bacteria on marinated chicken by essential oils under aerobic and vacuum packaging. Issue 1 (4th December 2022) - Osaili, Tareq M.; Al‐Nabulsi, Anas A.; Hasan, Fayeza; Dhanasekaran, Dinesh K.; Ismail, Leila Cheikh; Hashim, Mona; Hasan, Hayder; Ayyash, Mutamed; Olaimat, Amin; Hussain, Ayman Z. S.; Darra, Nada El; Savvaidis, Ioannis N.; et al.
Abstract : Abstract: "Chicken tawook" is a marinated boneless chicken entrée consumed in the Middle East. The aim of this study was to determine whether bioactive essential oil (EO) components carvacrol (CA), cinnamaldehyde (CI), and thymol (TH) would delay the growth of microorganisms causing tawook spoilage during aerobic (AP) or vacuum (VP) packed storage. The EOs at 1% and 2% were mixed individually with the marinade. The samples (10 g of chicken cubes with 1.2 g of marinade – with or without EOs) were stored in bags under AP and VP (Geryon ® ) for 7 days at 4 ± 1°C and abusive conditions (10 ± 1°C). Two control samples consisting of meat chunks and tawook without EO were used. The microflora numbers were greater at 10°C than at 4°C, and the marinade worked additively with AP against anaerobes, yeast and mold (Y & M) and lactic acid bacteria. It also worked additively with VP against aerobic bacteria recovered as Pseudomonas and the total plate count. EO components were observed to decrease microbial populations by a maximum of 4 to 6 log colony‐forming unit (CFU)/g depending on the type of microorganism. The combined mixture of marinade and 2% EO (CA, CI, and TH) resulted in the greatest reductions of all spoilage microorganisms at 10°C under AP on the last day of storage. Overall, VP was more effective ( p  < 0.05) than AP in controlling microorganisms at both 4 and 10°C. This study provides an affordable and natural alternative for extending product life. Practical Application: The use of EOs in marinated chicken (tawook) is expected to help producers reduce spoilage and extend shelf‐life of the product when stored at refrigeration temperatures. EOs provide a cheaper alternative and are naturally sourced. Vacuum packaging will increase the shelf‐life of marinated chicken tawook and facilitate its storage and transportation.